Effect and mechanism of calpains on pediatric lobar pneumonia. Issue 4 (4th July 2017) - Yin, Genquan; Zeng, Qiang; Zhao, Haijin; Wu, Peiqiong; Cai, Shaoxi; Deng, Li; Jiang, Wenhui
ABSTRACT: Lobar pneumonia, one of the community-acquired pneumonia (CAP), is a common pediatric low respiratory tract infection. Calpains are Ca 2+ -activated cysteine proteases whose activation mechanism is elusive. The present study was undertaken to detect the role and mechanism of calpains in pediatric lobar pneumonia. The human acute lung infection model (ALIM) was constructed and infected by Streptococcus . Enzyme-linked immunosorbent assay (ELISA) was used to measure interleukin (IL)-6, IL-8 and tumor necrosis factor (TNF)-α. We observed the lactate dehydrogenase (LDH) release, calpains activity and calpain inhibitor effects in ALIM. The expression of proliferating cell nuclear antigen (PCNA) protein was quantified by western blotting. Then the effects of calpain 1 and 2 knockdown on expressions of inflammation factors and PCNA protein, LDH release and apoptosis were evaluated in lung MRC-5 cells. In constructed ALIM, expressions of IL-6 ( P < 0.01), IL-8 ( P < 0.01), TNF-α ( P < 0.05) and PCNA protein ( P < 0.05) were significantly reduced by the calpain inhibitor. Expressions of IL-6, IL-8, TNF-α, PCNA protein and relative LDH release were statistically reduced by the small interfering (si) RNA-calpain 1 and 2 in MRC-5 cells ( P < 0.05). Calpains silence increased apoptotic cells from 5% (negative control) to more than 20% in MRC-5 cells. The present study suggests that calpains possess a significant effect on inflammations, cell proliferation and apoptosis. Suppression of calpains may provide a potential therapeutic target of lobar pneumonia.